Pujian Perspektif Hadis Nabi SAW (Suatu Kajian Mauḍu'i) - Ansyar, Siti Aisyah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Praise in Islam is not only a social expression, but also subject to the Shariah ethic which demands honesty, sincerity, and right intentions. Hadiths of the Prophet Muhammad. shows two sides of praise: there is one that allows it as a form of acknowledgment of one’s preference, and there is one that prohibits it if it is excessive.. This study elaborates on three items of problem formulation namely: First, what is the quality of the hadiths on praise. Second, how the hadiths understand praise. Third, what about the implications of the hadiths on praise. This type of research is qualitative using descriptive analysis methods. The researcher specifically uses a hadith science approach that is directly concerned with the interpretation of a text and aims to analyze the hadiths that are the object of the study. Data were obtained through library research by citing, consolidating, and analyzing against literature that was representative and relevant to the issue under discussion, then reviewing and summarizing it. The results of this study outline that: Firstly, the majority of hadith on praise is judged to be authentic because it fulfills the conditions of sanad and matan according to hadith science. However, the hadith praise to Allah swt. considered weak In contrast, the hadith on praise of the dead and the prohibition of excessive praising, is judged to be authentic. This finding suggests that the hadith warning against the dangers of praise have strong authenticity. Second, the hadith on praise teaches the importance of monotheism, speech etiquette, and social as well as spiritual awareness. The hadith on praise serves as a guide so that we can appreciate the goodness of others without forgetting that only Allah deserves absolute praise. Third, praise can be positively or negatively impactful, depending on its manner, timing, and intent. Praise that is appropriate, age-appropriate, and given after success can increase motivation, reinforce good behavior, and aid learning achievement, especially in children. Sincere praise also intensifies social relationships and creates a harmonious atmosphere.